Performance of Exotic Poplar in Tarai - Jha, Kaushalendra Kumar; Gupta, Chandra; Verma, R. S.; Chhimwal, C. B. (Indian Forester, 1993)
In search of promising clones suited to tbe Tarai climate a trial of sixty clones imported from five countries was laid in replicated randomised block design. Propagation medium was ETP. D-75, S7C20, S7C8 066, S7C15, S7CI 2502 and 69/5 turned to be the best suited ones. Most of these are American clones. Overall performance of Italian, Australian, Dutch and German clones were inferior. Rotation age of above promising clones should be reduced to 6-8 years if grown for pulp and intercropping.